2016
DOI: 10.3390/e18070271
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Characteristic Analysis and Experimental Study of a Spindle-Bearing System

Abstract: Abstract:In this paper, a thermo-mechanical coupling analysis model of the spindle-bearing system based on Hertz's contact theory and a point contact non-Newtonian thermal elastohydrodynamic lubrication (EHL) theory are developed. In this model, the effect of preload, centrifugal force, the gyroscopic moment, and the lubrication state of the spindle-bearing system are considered. According to the heat transfer theory, the mathematical model for the temperature field of the spindle system is developed and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Ge and Ding [5] utilized Carbon Fiber Reinforced Plastic (CFRP) with the performance of the thermal contraction to reduced thermal deformations of spindle housing. Li and Qingchang [6] indicated that the factors affecting the thermal error of the spindle included the oil-film thickness and the preload and lubrication of the bearing. By using a cooling system, the radial temperature difference of the spindle can be controlled within 30 • C even during operation at high rotational speeds.…”
Section: Temperature Difference T Imentioning
confidence: 99%
“…Ge and Ding [5] utilized Carbon Fiber Reinforced Plastic (CFRP) with the performance of the thermal contraction to reduced thermal deformations of spindle housing. Li and Qingchang [6] indicated that the factors affecting the thermal error of the spindle included the oil-film thickness and the preload and lubrication of the bearing. By using a cooling system, the radial temperature difference of the spindle can be controlled within 30 • C even during operation at high rotational speeds.…”
Section: Temperature Difference T Imentioning
confidence: 99%
“…Wu and Tan [10] have developed a thermo-mechanical coupling analysis model of the spindle-bearing system based on the Hertz's contact theory and the point contact non-Newtonian thermal elastohydrodynamic lubrication (EHL) theory.…”
Section: Overview Of the Previous Workmentioning
confidence: 99%
“…The distribution of temperature is the foundation of thermal-mechanical coupling model. There are usually two foundation methods to solve the temperature field, the thermal grid method [11][12][13] and the finite element method [14][15][16].…”
Section: Introductionmentioning
confidence: 99%